Review of the Efficacy and Mechanisms of Traditional Chinese Medicine for Treating Multi-Organ Damage in Wilson’s Disease - Chen H; Wang X; Tang L; Pu Y; Ma Y; Ye H; Zhang J (Drug Design, Development and Therapy)
Hong Chen,1,* Xie Wang,1,* Le Tang,2 Yue Pu,1 Ying Ma,1 Hao Ye,1 Juan Zhang1 1Department of Neurology, The First Affiliated Hospital of Anhui University of Traditional Chinese Medicine, Hefei, 230031, People’s Republic of China; 2Department of Neurology, Quanjiao County Hospital of Traditional Chinese Medicine, Chuzhou, 239599, People’s Republic of China*These authors contributed equally to this workCorrespondence: Juan Zhang, Department of Neurology, The First Affiliated Hospital of Anhui University of Traditional Chinese Medicine, 117 Meishan Road, Hefei, Anhui, People’s Republic of China, Email zhangdoumi2019@163.comAbstract: Wilson’s disease (WD) is an autosomal recessive disorder characterized by abnormal copper metabolism. Disruptions in copper metabolism lead to excessive copper deposition in the liver, nervous system, kidneys, heart, and other organs, thereby inducing a range of pathological manifestations and clinical symptoms. Traditional Chinese Medicine (TCM) has demonstrated significant therapeutic efficacy and excellent safety profiles. When integrated with effective Western anti-copper therapies, it can yield superior therapeutic outcomes. Consequently, TCM has exhibited unique advantages in managing WD, particularly when combined with multiple systemic damages. This paper discusses the pathological mechanisms and TCM etiology and pathogenesis of WD combined with multiple organ damage. It also summarizes the clinical efficacy and mechanism of TCM in treating WD combined with multiple organ damage, aiming to provide a reference for further studies on the role and potential mechanisms of TCM interventions in WD.Keywords: Wilson’s disease, copper, traditional Chinese medicine, multiple organ damage, mechanism